Composite electrolyte for protecting positive electrode and negative electrode of zinc ion battery and application of composite electrolyte

By using a composite electrolyte of ethylene glycol and water in zinc ion batteries, the problem of poor cycle stability of zinc ion batteries is solved, and higher cycle life and electrochemical performance are achieved, reducing development costs and environmental impacts.

CN119725792AInactive Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +1

Patent Information

Application Number
CN202311268955.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the recycling process of zinc ion batteries, there are problems such as dissolution of the positive electrode material and dendrites of the zinc negative electrode, resulting in poor circulation stability and safety hazards.

Method used

A mixed solvent of ethylene glycol and water is used as the solvent of the composite electrolyte. The volume ratio of ethylene glycol to water is 2:8 to 7:3. The first solvated shell layer of Zn2+ is entered through ethylene glycol, reducing the activity of water and inhibiting the loss of the positive electrode material.

Benefits of technology

It effectively inhibits the dissolution of the cathode material vanadium pentoxide, significantly improves the cycle life and electrochemical performance of zinc ion batteries, and reduces the battery development cost and environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004474985390000011
    Figure HDA0004474985390000011
  • Figure HDA0004474985390000012
    Figure HDA0004474985390000012
  • Figure HDA0004474985390000021
    Figure HDA0004474985390000021
Patent Text Reader

Abstract

The invention discloses a composite electrolyte for protecting a positive electrode and a negative electrode of a zinc ion battery and application of the composite electrolyte, the composite electrolyte comprises zinc salt and a solvent, the solvent is a mixture of ethylene glycol and water, and the volume ratio of the ethylene glycol to the water is 2: 8-7: 3. Compared with the traditional aqueous electrolyte, the electrolyte provided by the invention has the advantages that the solvation structure of zinc ions can be optimized, and the dissolution of a vanadium-based compound is effectively inhibited, so that the cycling stability of the zinc ion battery is greatly improved. It needs to be pointed out that the electrolyte is simple in preparation method, mild in reaction condition, low in cost and extremely easy to prepare in a large scale, and has an excellent application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a novel composite electrolyte for zinc ion batteries which can provide excellent cycle stability and a preparation method thereof, and belongs to the field of materials. Background Art

[0002] The development of clean and efficient renewable energy has become a global hot topic. Lithium-ion batteries are favored due to their high energy and long life, and are now widely used in various electronic devices. However, due to the low natural abundance and poor safety performance of lithium-ion batteries, it is urgent to develop new low-cost and environmentally friendly battery energy storage technologies. Among the many new secondary batteries, aqueous zinc-ion batteries have attracted widespread attention from researchers due to their many advantages such as low cost, high capacity, and high safety, becoming the next generation of energy storage systems with great application potential.

[0003] However, the commercial application of zinc-ion batteries still faces acute challenges. 2+ With a high charge density, it is easy to produce strong electrostatic interactions with vanadium-based, manganese-based and other positive electrode materials, thereby accelerating their structural collapse and causing serious performance degradation; on the other hand, the high activity of water molecules in aqueous electrolytes can easily lead to problems such as rapid dissolution of positive electrode materials, dendrites at the zinc negative electrode, and hydrogen evolution, which greatly reduces the cycle stability of the battery and is more likely to cause safety hazards such as battery short circuits and bulging. Therefore, it is urgent to develop a new electrolyte that can reduce the activity of aqueous electrolytes, inhibit the dissolution of positive electrode materials, and prevent dendrites at the zinc negative electrode. Summary of the invention

[0004] The invention provides a composite electrolyte for improving the cycle life of a zinc ion battery. The composite electrolyte is a mixed solution of a zinc salt and a solvent. The solvent is a mixed solution of ethylene glycol and water. The volume ratio of ethylene glycol to water is 2:8 to 7:3.

[0005] Furthermore, in the above technical solution, ethylene glycol can replace some water molecules to enter Zn 2+ The strong interaction between water and ethylene glycol in the solvent reduces the activity of water, which is beneficial to improving the water retention capacity of the electrolyte and inhibiting the loss of vanadium-based compounds, the active material of the positive electrode, greatly improving the cycle performance of the battery.

[0006] Furthermore, in the above technical solution, the inorganic solvent is ultrapure water.

[0007] Furthermore, in the above technical solution, the organic solvent is ethylene glycol.

[0008] Furthermore, in the above technical solution, the ratio of the organic solvent to the inorganic solvent in the composite electrolyte is 2:8 to 7:3.

[0009] Furthermore, in the above technical solution, the zinc salt in the composite electrolyte is one or more of zinc chloride, zinc nitrate, zinc trifluoromethanesulfonate, zinc sulfate, zinc acetate, and zinc perchlorate.

[0010] Furthermore, in the above technical solution, the concentration of zinc salt in the composite electrolyte is 1mL -1 ~3M L -1 .

[0011] The present invention provides a composite electrolyte that can effectively inhibit the dissolution of a positive electrode vanadium-based material, and the preparation method thereof comprises the following steps:

[0012] (1) Weigh a certain amount of zinc salt ZnX n , where X = Cl - 、SO4 2- 、NO3 - 、CH3COO - CF3SO3 - 、ClO4 - One or more of, n = 1 to 2, the molar concentration of the zinc salt is 0 to 6 M L -1 .

[0013] (2) Weigh a certain amount of ethylene glycol and aqueous solution respectively, and stir and mix the two evenly. The volume ratio of ethylene glycol to water can be one or more of 2:8, 3:7, 6:4, and 7:3.

[0014] (3) Add the zinc salt in step (1) to the solution in step (2) and stir until a transparent and clear liquid is obtained.

[0015] The present invention provides application of the composite electrolyte in a zinc ion battery.

[0016] The composite electrolyte prepared by the present invention is used to evaluate the cycle stability of the zinc ion battery, and the process is as follows:

[0017] The positive electrode - vanadium pentoxide and the negative electrode - zinc sheet are placed in the corresponding positions of the button battery, and the prepared composite electrolyte is added after the separator is placed in the middle. Finally, the battery is packaged using a sealing machine. The packaged battery is connected to an electrochemical charge and discharge instrument and the current density (0.5-5Ag) is specified. -1 ) was used to conduct a cyclic stability test.

[0018] Beneficial results: Compared with the prior art, the present invention has the following significant advantages:

[0019] (1) The composite electrolyte can effectively inhibit the dissolution of the positive electrode material, vanadium pentoxide, and greatly improve the cycle life, showing more excellent electrochemical performance;

[0020] (2) The preparation method of the composite electrolyte is simple and low-cost, which is conducive to large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The aqueous electrolyte and the composite electrolyte in the Zn||V2O5 full cell, 0.5A g -1 The cycle performance curve below.

[0022] Figure 2 This is a scanning electron microscope image of the positive electrode material - V2O5 after 200 cycles when the volume content of ethylene glycol is 20%.

[0023] Figure 3 This is a scanning electron microscope image of the positive electrode material, V2O5, after 75 cycles when the volume content of ethylene glycol in Example 2 is 30%.

[0024] Figure 4 This is a scanning electron microscope image of the positive electrode material, V2O5, after 80 cycles when the volume content of ethylene glycol in Example 3 is 60%.

[0025] Figure 5 This is a scanning electron microscope image of the positive electrode material, V2O5, after 150 cycles when the volume content of ethylene glycol in Example 4 is 70%.

[0026] Figure 6 This is a scanning electron microscope image of the positive electrode material, V2O5, after 389 cycles when the volume content of ethylene glycol in Example 5 is 0%.

[0027] Figure 7 This is a scanning electron microscope image of the positive electrode material, V2O5, after 115 cycles when the volume content of ethylene glycol in Example 5 is 100%.

[0028] Figure 8 The electrolyte used in Example 6 is 1mL -1 When the volume content of zinc trifluoromethanesulfonate and ethylene glycol is 30%, in the Zn||V2O5 full battery, 0.5Ag -1 The cycle performance curve below.

[0029] Fig. 9 The electrolyte used in Example 6 is 1mL -1 Scanning electron microscope image of the positive electrode material - V2O5 after 45 cycles when the volume content of ethylene glycol is 30% with zinc trifluoromethanesulfonate.

[0030] Fig.10 The electrolyte used in Example 7 is 1mL -1 When the volume content of zinc chloride and ethylene glycol is 30%, in the Zn||V2O5 full battery, 5A g -1The cycle performance curve below.

[0031] Fig.11 The electrolyte used in Example 7 is 1mL -1 When the volume content of zinc chloride and ethylene glycol is 30%, in the Zn||V2O5 full battery, 5A g -1 Scanning electron microscope image of the positive electrode material - V2O5 after 5000 cycles.

[0032] Fig.12 The electrolyte used in Comparative Example 1 is 1 mL -1 Zinc chloride, ethylene glycol-free aqueous zinc chloride solution, in Zn||V2O5 full cell, 0.5Ag -1 The cycle performance curve below.

[0033] Fig.13 The electrolyte used in Comparative Example 2 is 1mL -1 Zinc chloride, zinc chloride ethylene glycol solution without water, in Zn||V2O5 full cell, 0.5Ag -1 Scanning electron microscope image of the positive electrode material - V2O5 after 12 cycles.

[0034] Fig.14 The electrolyte used in Comparative Example 3 is 1mL -1 Zinc chloride, non-aqueous zinc chloride methanol solution Zn||V2O5 full battery, 0.5Ag -1 Scanning electron microscope image of the positive electrode material - V2O5 after 2 cycles. DETAILED DESCRIPTION

[0035] The following examples will further illustrate the present invention, but are not intended to limit the invention.

[0036] The battery assembly in the following examples or comparative examples is as follows: the positive electrode - vanadium pentoxide and the negative electrode - zinc sheet are placed in the corresponding positions in the button battery, a separator is placed in the middle and the prepared composite electrolyte is added, and finally the battery is packaged using a sealing machine. The packaged battery is connected to an electrochemical charge and discharge instrument and the current density (0.5-5Ag) is specified. -1 ) was used to conduct a cyclic stability test.

[0037] Example 1

[0038] Prepare zinc chloride concentration of 1 mL -1 , zinc chloride composite electrolyte with ethylene glycol volume fraction of 20%:

[0039] Weigh 1.363g of zinc chloride into a beaker, add 2mL of ethylene glycol, and then add 8mL of ultrapure water, stirring until the zinc chloride particles are completely dissolved; after dissolution, continue stirring to mix evenly. Its cyclic stability is shown in Figure 1 After the cycle, the electron microscope morphology of the positive electrode material - vanadium pentoxide is shown Figure 2 .

[0040] Example 2

[0041] Prepare zinc chloride concentration of 1 mL -1 , zinc chloride composite electrolyte with 30% ethylene glycol volume fraction:

[0042] Weigh 1.363g of zinc chloride into a beaker, add 3mL of ethylene glycol, and then add 7mL of ultrapure water, stirring until the zinc chloride particles are completely dissolved; after dissolution, continue stirring to mix evenly. -1 The cycling stability is shown in Figure 1 After 75 cycles, the electron microscope morphology of the positive electrode material - vanadium pentoxide is shown Figure 3 .

[0043] Example 3

[0044] Prepare zinc chloride concentration of 1 mL -1 , zinc chloride composite electrolyte with 60% ethylene glycol volume fraction:

[0045] Weigh 1.363 g of zinc chloride into a beaker, add 6 mL of ethylene glycol, and then add 4 mL of ultrapure water, stirring until the zinc chloride particles are completely dissolved; after dissolution, continue stirring to mix evenly. -1 The cycling stability is shown in Figure 1 After the cycle, the electron microscope morphology of the positive electrode material - vanadium pentoxide is shown Figure 4 .

[0046] Example 4

[0047] Prepare zinc chloride concentration of 1 mL -1 , zinc chloride composite electrolyte with ethylene glycol volume fraction of 70%:

[0048] Weigh 1.363 g of zinc chloride into a beaker, add 7 mL of ethylene glycol, and then add 3 mL of ultrapure water, stirring until the zinc chloride particles are completely dissolved; after dissolution, continue stirring to mix evenly. -1 The cycling stability is shown in Figure 1 After the cycle, the electron microscope morphology of the positive electrode material - vanadium pentoxide is shown Figure 5 .

[0049] Example 5

[0050] Prepare zinc trifluoromethanesulfonate at a concentration of 1 mL -1 , trifluoromethanesulfonate zinc composite electrolyte with 30% ethylene glycol volume fraction:

[0051] Weigh 3.6353g of zinc chloride into a beaker, add 3mL of ethylene glycol, and then add 7mL of ultrapure water, stirring until the zinc trifluoromethanesulfonate particles are completely dissolved; after dissolution, continue stirring to mix evenly. -1 The cycling stability is shown in Figure 6 After the cycle, the electron microscope morphology of the positive electrode material - vanadium pentoxide is shown Figure 7 .

[0052] Example 6

[0053] Prepare zinc chloride concentration of 1 mL -1 , zinc chloride composite electrolyte with 30% ethylene glycol volume fraction:

[0054] Weigh 1.363 g of zinc chloride into a beaker, add 3 mL of ethylene glycol, and then add 7 mL of ultrapure water, stirring until the zinc chloride particles are completely dissolved; after dissolution, continue stirring to mix evenly. -1 The cycling stability is shown in Figure 8 After 75 cycles, the electron microscope morphology of the positive electrode material - vanadium pentoxide is shown Fig. 9 . It still maintains good cycle performance at high current density.

[0055] Example 7

[0056] Prepare zinc chloride concentration of 1 mL -1 , zinc chloride composite electrolyte with 30% ethylene glycol volume fraction:

[0057] Weigh 1.363g of zinc chloride into a beaker, add 3mL of ethylene glycol, and then add 7mL of ultrapure water, stirring until the zinc chloride particles are completely dissolved; after dissolution, continue stirring to mix evenly. -1 The cycling stability is shown in Fig.10 After 12 cycles, the electron microscope morphology of the positive electrode material - vanadium pentoxide is shown Fig.11 ; Usually at a higher current density, due to the faster charge and discharge process, the electrolyte with lower conductivity contains Zn 2+The possibility of not being able to complete the embedding and unembedding results in too low capacity and poor stability. However, in this embodiment, in the electrolyte containing 30% ethylene glycol, the conductivity of the electrolyte and the regulation of the water content are taken into account, so that it is 5Ag -1 It can still maintain high capacity and stable cycle performance under high current density.

[0058] Comparative Example 1

[0059] Prepare zinc chloride concentration of 1 mL -1 Aqueous zinc chloride solution without ethylene glycol:

[0060] Weigh 1.363g of zinc chloride into a beaker, add 10mL of water, and stir until the zinc chloride particles are completely dissolved; after dissolution, continue stirring to mix evenly. -1 The cycling stability is shown in Figure 1 After the cycle, the electron microscope morphology of the positive electrode material - vanadium pentoxide is shown Fig.12 In pure water electrolyte, due to the presence of excess water, it is very easy to cause the positive electrode active material to dissolve during the charge and discharge process, and hydrogen evolution reaction to occur at the negative electrode interface, resulting in poor cycle stability and obvious damage to the morphology of the positive electrode active material after cycling.

[0061] Comparative Example 2

[0062] Prepare zinc chloride concentration of 1 mL -1 Non-aqueous zinc chloride solution in ethylene glycol:

[0063] Weigh 1.363g of zinc chloride into a beaker, add 10mL of ethylene glycol, and stir until the zinc chloride particles are completely dissolved; after dissolution, continue stirring to mix evenly. -1 The cycling stability is shown in Figure 1 After the cycle, the electron microscope morphology of the positive electrode material - vanadium pentoxide is shown Fig.13 In pure ethylene glycol electrolyte, the side reactions caused by active water are effectively eliminated, making the charge-discharge cycle performance relatively stable; the electron microscopy results of the positive electrode active material after the cycle also confirmed this mechanism; but due to the high viscosity of ethylene glycol, the conductivity is low, so the charge-discharge specific capacity is relatively low.

[0064] Comparative Example 3

[0065] Prepare zinc chloride concentration of 1 mL -1 Non-aqueous zinc chloride methanol solution:

[0066] Weigh 1.363 g of zinc chloride into a beaker, add 3 mL of methanol, and then measure 7 mL of ultrapure water and add it, stirring until the zinc chloride particles are completely dissolved; after dissolution, continue stirring to mix evenly. -1 The current density was cycled for 2 cycles. After 2 cycles, the electron microscope morphology of the positive electrode material - vanadium pentoxide in the discharge state was shown in Fig.14 As shown in the figure, in the discharge state, by-products can still be formed in the methanol electrolyte without water, which is not conducive to the long-term stability of the battery.

Claims

1. A composite electrolyte for improving the cycle life of a zinc ion battery, characterized in that: The composite electrolyte is a mixture of zinc salt and solvent, the solvent is a mixture of ethylene glycol and water, and the volume ratio of ethylene glycol to water is 2:8-7:

3.

2. The composite electrolyte according to claim 1, characterized in that: The composite electrolyte can regulate the solvation structure of zinc ions and effectively inhibit the dissolution of vanadium-based compounds.

3. The composite electrolyte according to claim 1, characterized in that: The inorganic solvent is ultrapure water.

4. The composite electrolyte according to claim 1, characterized in that: The organic solvent is ethylene glycol.

5. The composite electrolyte according to claim 1, characterized in that: The ratio of the organic solvent to the inorganic solvent in the composite electrolyte is 2:8 to 7:

3.

6. The composite electrolyte according to claim 1, characterized in that: The zinc salt in the composite electrolyte is one or more of zinc chloride, zinc nitrate, zinc trifluoromethanesulfonate, zinc sulfate, zinc acetate, and zinc perchlorate.

7. The composite electrolyte according to claim 1, characterized in that: The concentration of zinc salt in the composite electrolyte is 1ML -1 ~3M L -1 .

8. Use of the composite electrolyte according to any one of claims 1 to 7 in a zinc ion battery.

Citation Information

Patent Citations

  • Aqueous zinc ion battery electrolyte capable of protecting vanadium-containing compound positive electrode and application of aqueous zinc ion battery electrolyte

    CN113097576A

  • Mixed electrolyte of aqueous zinc ion battery

    CN113725500A

  • Preparation and application of aqueous zinc ion battery electrolyte

    CN114447445A

  • Aqueous electrolyte and battery

    CN115312879A

  • Preparation method of low-temperature-resistant zinc battery composite electrolyte

    CN115995617A

Cited By

  • Wide-temperature-range aqueous zinc ion battery electrolyte and preparation method thereof

    CN121394610A